O025/#522 Maintenance olaparib rechallenge in patients with ovarian cancer previously treated with a parp inhibitor: patient-reported outcomes from the phase IIIB OReO/engot-ov38 trial. (4th December 2022) - Redondo, Andrés; Follana, Philippe; Scambia, Giovanni; Asselain, Bernard; Marmé, Frederik; Mirza, Mansoor; Laudani, Maria Elena; Mądry, Radosław; Glasspool, Rosalind; You, Benoit; Rubio-Perez, María Jesús; Zamagni, Claudio; et al.
Abstract : Objectives: In OReO/ENGOT-ov38 (NCT03106987 ), maintenance olaparib rechallenge significantly improved progression-free survival (PFS) versus placebo in platinumsensitive relapsed ovarian cancer (PSROC), irrespective of BRCA1/BRCA2 mutation (BRCAm) status (BRCAm: hazard ratio [HR] 0.57, 95% confidence interval [CI] 0.37–0.87; P=0.022; non-BRCAm: HR 0.43, 95% CI 0.26–0.71; P=0.002) (PujadeLauraine et al. ESMO 2021). We assessed health-related quality of life (HRQoL) by patient-reported outcomes (PROs). Methods: Patients with PSROC, prior PARP inhibitor maintenance (one line), and in response to last platinum-based chemotherapy were randomized (BRCAm and non-BRCAm cohorts) to maintenance olaparib (300 mg bid) or placebo until progression. Prespecified secondary PROs included change from baseline in Functional Assessment of Cancer Therapy-Ovarian (FACT-O) Trial Outcome Index (TOI), and best response and improvement in TOI. The minimally important difference (MID) for clinically meaningful change in TOI was 10 points. Results: Patients were randomized in cohorts (BRCAm: olaparib=74, placebo=38; non-BRCAm: olaparib=72, placebo=36). The difference between olaparib and placebo in the overall adjusted mean change in TOI score was not considered clinically meaningful in either cohort as 95% CIs lay within the MID interval: BRCAm, -2.94 (95% CI -4.99 to -0.90); non-BRCAm, -2.66 (95% CI -4.75 to -0.58) ( figure 1 ). Most olaparib and placebo patients had a best response of no change in TOI; no significant differences in proportion with improvement in TOI were observed ( table 1 ). Few olaparib and placebo patients had a TOI deterioration: BRCAm, 10 (14%) and 4 (11%); non-BRCAm, 10 (15%) and 2 (6%). Conclusions: Maintenance olaparib rechallenge significantly improved PFS over placebo, without clinically meaningful change in HRQoL. Clinical trial ID: NCT03106987